1991
DOI: 10.1128/jb.173.2.810-815.1991
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the cIII gene of bacteriophage HK022

Abstract: The clII gene product of lambdoid bacteriophages promotes lysogeny by stabilizing the phage-encoded CII protein, a transcriptional activator of the repressor and integrase genes. Previous works showed that the synthesis of the bacteriophage A CIII protein has specific translational requirements imposed by the structure of the mRNA. To gain insight into the mRNA structure and its role in regulating cIII translation, we undertook a mutational analysis of the cIII gene of the related bacteriophage HK022. Our data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Mutants T58, A60, and A70 of the HK022 cIII gene were isolated as clones that grow normally even in the presence of IPTG. Protein labeling experiments demonstrated that these clones efficiently synthesize CIII protein (9). As shown in Table 1, the mutations also relieved the inhibition of growth of an infecting A cIII-phage.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Mutants T58, A60, and A70 of the HK022 cIII gene were isolated as clones that grow normally even in the presence of IPTG. Protein labeling experiments demonstrated that these clones efficiently synthesize CIII protein (9). As shown in Table 1, the mutations also relieved the inhibition of growth of an infecting A cIII-phage.…”
Section: Resultsmentioning
confidence: 88%
“…Overexpression of the plasmid-encoded cIII gene induced by the addition of IPTG to the plate leads to a strong reduction in the growth rate of the host cell, yielding barely visible colonies (8,9). Mutants T58, A60, and A70 of the HK022 cIII gene were isolated as clones that grow normally even in the presence of IPTG.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations